The Kingdom of Banggai and the reorganization of administrative regions: a perspective in maritime history - Zuhdi, Susanto; Sadi, Haliadi; Pradjoko, Didik (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article analyzed the historical dynamic found in the Kingdom of Banggai, Central Sulawesi, following the issue regarding the reorganization of administrative regions, from the perspective of maritime history. According to the traditional sailing routes in Maluku Sea, as mentioned in Nagarakartagama (1365), Banggai was one of the main ports that played significant role in portto-port interconnectivity in Eastern Sulawesi. However, the administrative reorganization in 1998’s Reformasi had disrupted the kingdom’s territorial unit into various New Autonomous Regions (Daerah Otonomi Baru/DOB). Three DOBs were being established, reintroducing the territorial unit as separated units with distinct characteristics. Banggai District was the parent unit in 1960s, with Luwuk chosen as its capital city in the mainland Sulawesi, with an active port that linked local, regional, and international trading routes. Banggai Kepulauan District was established later in 2004, along with its own port, Salakan Port, which served as its capital city as well. In 2013, Banggai Laut District was established, with administrative its area covering the original territory of the kingdom in the 14th century. The kingdom was stellarly noted for its port, serving routes to Gorontalo, Ternate, Buton, and Sula Islands. Within the framework of nation-state formation, such maritime linkage should be noticed in the infrastructural discussion on the nation-state building of Indonesia. The diaspora of the Bugis-Makassar, Buton, Mandar, Bajau, and others arriving from the Eastern Nusantaran Archipelago were bound to the development of Banggai people. The kingdom’s tradition and values of life continued to exist and should be further seen as a cohesion within Banggai people, both in social and cultural domains. Therefore, the reorganization of the administrative region in Banggai should not necessarily impair the existing maritime linkage.